FACTORS INFLUENCING THE FORMATION AND MAGNITUDE OF PHYSICAL AND MECHANICAL PROPERTIES OF COMPOSITE WOOD-PLASTIC MATERIALS AND BOARDS - 1д. К. Холмуродова.; Д. Ш. Киямова (Galaxy International Interdisciplinary Research Journal, 2023)
Taking into account that in this work the technology for the manufacture of composite wood-plastic materials and boards from cotton stalks is based on the principle used in the production of chipboards, information on chipboard was used in the analysis of technological factors